Genetic polymorphism of vitamin D receptors and plasminogen activator inhibitor‐1 and osteonecrosis risk in childhood acute lymphoblastic leukemia. Issue 7 (27th May 2021) - Sherief, Laila M.; Beshir, Mohamed; Raafat, Nermin; Abdelkhalek, Elhamy R.; Mokhtar, Wesam A.; Elgerby, Khaled M.; Soliman, Basma K.; Salah, Hosam E.; Mokhtar, Ghada A.; Kamal, Naglaa M.; ELsayed, Heba; Zakaria, Marwa
Abstract: Background: Osteonecrosis (ON) is one of the major therapy‐related complications in childhood acute lymphoblastic leukemia (ALL). The purpose of the current study is to assess the frequency of ON in children with ALL and to detect whether polymorphisms in vitamin D receptor gene (VDR) and plasminogen activator inhibitor‐1 (PAI‐1) gene can affect the risk of ON. Patients and Methods: Nighty‐six ALL children were enrolled. Serum 25‐hydroxyvitamin D 25(OH)D levels were performed in addition to the detection of polymorphisms in PAI‐1and VDR genes by polymerase chain reaction. Results: Ten out of 96 patients had ON (four males and six females aged above 10 years) and had an insufficient level of 25(OH)D. Fifty‐two percent of patients had PAI‐1 GG genotype while 48% had PAI‐1 GA genotype. PAI‐1 polymorphism was detected in 60% of all ON cases. The frequencies of VDR genotypes were CT (56.3%), CC (39.6%), and TT (4.2%). Osteonecrosis was found in eight patients with CC genotype and in two patients with CT genotype. Conclusion: Osteonecrosis can develop early during the therapy of ALL. Older age and insufficient level of 25(OH)D were considered important risk factor for the development of osteonecrosis. PAT‐1 and VDR gene polymorphism may be a genetic risk factor in its pathogenesis. Abstract : Osteonecrosis can develop early during the therapy of ALL. Older age and insufficient level of 25(OH)D were considered an important risk factor for the development of osteonecrosis. PAT‐1 and VDR gene polymorphism may be a genetic risk factor in its pathogenesis.